Morphological and phylogenetic analyses reveal two novel species of Curvularia (Pleosporales, Pleosporaceae) from southern China - Zhuan-Jun Guo; Mawuli Korsi Amenyogbe; Shi-Qiang Chen; Younes M. Rashad; Jian-Xin Deng; Huan Luo (MycoKeys)
Members of Curvularia are of widespread clinical and agricultural importance, but species identification remains challenging due to morphological similarities and environmental variation. In this study, nine Curvularia strains were isolated from diseased leaves of Nelumbo nucifera and Nicotiana tabacum in Guangxi and Guizhou provinces, China. Morphological characteristics and phylogenetic analyses based on ITS, GAPDH, and tef1-α sequences revealed two novel species of Curvularia s. str., described here as C. nuciferae sp. nov. and C. tabaci sp. nov. This study enhances understanding of Curvularia taxonomy and expands the known species diversity.